Involvement of V1-type vasopressin receptors on NaCl intake by hyperosmotic rats treated with muscimol in the lateral parabrachial nucleus - Callera, João C. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José V. [UNESP] (Elsevier, 2022)
GABAA receptor activation with agonist muscimol in the lateral parabrachial nucleus (LPBN) induces 0.3 M NaCl intake. In the present study, we investigated water and 0.3 M NaCl intake in male adult rats treated with losartan (angiotensin AT1 receptor antagonist) or MeT-AVP (V1-type vasopressin receptor antagonist) combined with muscimol or methysergide (5-HT2 antagonist) into the LPBN in rats treated with intragastric 2 M NaCl. After 2 M NaCl load and bilateral injections of muscimol (0.5 nmol/0.2 µL) into the LPBN, rats ingested water and 0.3 M NaCl. The pre-treatment of the LPBN with MeT-AVP (1 nmol/0.2 µL) but not losartan (50 µg/0.2 µL) in muscimol treated rats reduced 0.3 M NaCl intake. The pre-treatment of the LPBN with MeT-AVP did not modify the increased 0.3 M NaCl intake in rats treated with methysergide (4 µg/0.2 µL), suggesting that the effect of MeT-AVP was not due to non-specific inhibition of ingestive behavior. The results suggest that endogenous vasopressin in the LPBN facilitates the effects of GABAergic activation driving cell-dehydrated male rats to ingest 0.3 M NaCl.
Keywords: Dehydration; GABAA receptor; Osmoreceptor; Sodium appetite; Thirst